2008
DOI: 10.1038/ncpneuro0941
|View full text |Cite
|
Sign up to set email alerts
|

Nerve damage in leprosy and its management

Abstract: Leprosy is the most common treatable peripheral nerve disorder worldwide. Deformity and disability result from nerve-function impairment; however, early treatment is associated with good outcome. Leprosy is often diagnosed late as many physicians have little experience with the clinical picture. Recent research using nerve conduction and thermal threshold tests has identified that nerve impairment is detectable long before it turns clinical. This discovery could have important implications for treatment becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 31 publications
7
68
1
3
Order By: Relevance
“…This association was also observed by Gonçalves et al (2008) [24]. Peripheral nerve injury has been associated with physical disability and is considered to be the most serious complication of leprosy [2,8,25]. Studies conducted in India [3,19], Bangladesh [26], and Brazil [24] have shown that patients with three or more affected nerves are more likely to develop disabilities.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This association was also observed by Gonçalves et al (2008) [24]. Peripheral nerve injury has been associated with physical disability and is considered to be the most serious complication of leprosy [2,8,25]. Studies conducted in India [3,19], Bangladesh [26], and Brazil [24] have shown that patients with three or more affected nerves are more likely to develop disabilities.…”
Section: Discussionsupporting
confidence: 50%
“…The impairment of nerve trunks has the potential to cause physical disabilities due to the immune system's action against the bacillus [6]. Its extent depends on the clinical form of the disease and the exacerbation phenomena during leprosy reaction episodes [7,8] Information on the number of people with disabilities/deformities due to leprosy remains limited. Only estimates of the number of individuals living with disabilities are available.…”
Section: Introductionmentioning
confidence: 99%
“…Leprosy is often diagnosed late, when permanent impairment has already occurred. Even after completion of treatment a significant proportion of patients sustain disabilities; resulting in the double burden of disability and disability induced stigma [36].This in turn has accumulated the stigma burden in society despite leprosy elimination in countries like Nepal. This psycho-social process of stigma has rendered stigma a cyclic process of complex phenomenon which does not only necessitate the disease treatment but the meticulous interventions to reduce stigma, disability prevention and rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Self or internalized stigma is in fact a long term impact of continuous socialization about stigmatization which leads to the development of loss of self-esteem and dignity along with the consequent development of fear, shame, hopelessness and guilt [36]. Mixed stigma in this review refers to the stigma which includes more than one type of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Demyelination occurring as a sequel to atrophic changes in the axonal component and physiologic damage due to persistence of mycobacterial antigens in the Schwann cells or axons is responsible for more diffuse, insidious and gradually progressive NFI. [32] Within what period after the onset of nerve damage should corticosteroid therapy begin and how long to continue remains unanswered?…”
Section: Treatment Of Nerve Function Impairment (Nfi) Treatment Of Nementioning
confidence: 99%